Platelets mediate increased endothelium permeability in dengue through NLRP3-inflammasome activation - Hottz, Eugenio D.; Lopes, Juliana F.; Freitas, Carla; Valls-de-Souza, Rogério; Oliveira, Marcus F.; Bozza, Marcelo T.; Da Poian, Andrea T.; Weyrich, Andrew S.; Zimmerman, Guy A.; Bozza, Fernando A.; Bozza, Patricia T. (Blood, 2013)
Dengue is the most frequent hemorrhagic viral disease and re-emergent infection in the world. Although thrombocytopenia is characteristically observed in mild and severe forms of dengue, the role of platelet activation in dengue pathogenesis has not been fully elucidated. We hypothesize that platelets have major roles in inflammatory amplification and increased vascular permeability during severe forms of dengue. Here we investigate interleukin (IL)-1β synthesis, processing, and secretion in platelets during dengue virus (DV) infection and potential contribution of these events to endothelial permeability during infection. We observed increased expression of IL-1β in platelets and platelet-derived microparticles from patients with dengue or after platelet exposure to DV in vitro. We demonstrated that DV infection leads to assembly of nucleotide-binding domain leucine rich repeat containing protein (NLRP3) inflammasomes, activation of caspase-1, and caspase-1–dependent IL-1β secretion. Our findings also indicate that platelet-derived IL-1β is chiefly released in microparticles through mechanisms dependent on mitochondrial reactive oxygen species–triggered NLRP3 inflammasomes. Inflammasome activation and platelet shedding of IL-1β–rich microparticles correlated with signs of increased vascular permeability. Moreover, microparticles from DV-stimulated platelets induced enhanced permeability in vitro in an IL-1–dependent manner. Our findings provide new evidence that platelets contribute to increased vascular permeability in DV infection by inflammasome-dependent release of IL-1β. •Dengue infection triggers functional inflammasome assembly in platelets.•Platelets may contribute to increased vascular permeability in dengue virus infection by synthesis and release of IL-1β.